(3QSGdI aj Gdabgs
(3ChdgG (B:s
(3Yde HCf GdYHO eHJdi Hjf Cf jWjY Gddg ajKGH hCf jYUjg ajYGbH s
(3BNQgG (B:s
(3GSJNQGL gPg GdCMcGe ef GdeMjW hGdYbGFO GdcHQi hGdgOGjI Je abO CcHQ s
(3Vef eLehY s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdbQGAGJ hGdJLhjOs